Dysplasia epiphysealis hemimelica of the radial head: a rare case report - Hiva Mohamadian; Mansour Bahardoust; Borzouyeh Molazem Sanandaji; Saba Saberi (BMC Musculoskeletal Disorders, 2021)
Abstract Background Dysplasia epiphysealis hemimelica (DEH) is a rare benign overgrowth generally affecting the epiphyses and short bones of the lower limbs. DEH in the elbow joint is extremely rare, and to date, only three cases of DEH have been reported in the radial head. Case presentation In this study, we report a case of DEH located in the radial head of the right elbow of a 10-year-old boy, which was presented with elbow pain and limited range of motion. In clinical examination, an asymmetrical enlargement was observed over the elbow. The lesion was resected surgically, and the patient’s symptoms resolved afterward. The histologic analysis of the lesion confirmed the diagnosis of DEH. Conclusion This report highlights the role of DEH in the differential diagnosis of elbow pathologies, particularly its differentiation from osteochondroma.